Studi Kritis Bahan Ajar Akidah Akhlak Materi Hubuddunya Kelas X MA Yaspi Cicantayan - Salma Tsana Fi Saadah; Siti Qomariyah; Emi Tresnawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The concept of hubuddunya (love of the world) within the Akidah Akhlak subject holds a strategic role in shaping the moral and spiritual character of students, particularly in the midst of globalization, materialism, and consumerist culture that increasingly influence young generations. This study seeks to critically analyze the teaching materials of Akidah Akhlak for Grade X at MA YASPI Cicantayan, focusing on the hubuddunya topic. The main objective is to evaluate the relevance, depth, and effectiveness of these materials in fostering students’ awareness of moral values, as well as their ability to apply Islamic principles in daily life. This research employs a qualitative approach with a descriptive method, collecting data through documentation of learning resources, observation of lesson plans (RPP), and in-depth interviews with teachers. The data analysis process was conducted through reduction, classification, and interpretation of findings to obtain a comprehensive picture of the existing instructional practices. The results reveal that the current teaching materials tend to remain highly theoretical and emphasize the transfer of knowledge rather than transformative learning. Consequently, they do not adequately address contextual issues faced by students in their real-life environment. The affective and psychomotor aspects of students’ moral development are not optimally stimulated, leaving a gap between conceptual understanding and practical application. Furthermore, essential Islamic values such as zuhud (detachment from excessive worldliness), qanaah (contentment), and tawakal (trust in God) have not been integrated effectively as counterbalances to materialistic tendencies. The implications of this study underline the urgency of developing Akidah Akhlak teaching materials that are more contextual, student-centered, and relevant to contemporary challenges. Such materials should not only transmit religious knowledge but also foster reflective thinking, emotional maturity, and behavioral consistency, thereby preparing students to face globalization with strong faith, resilience, and anti-materialistic attitudes.